Reconstruction of the complete mitogenomes of predator and prey from a faecal metagenomic dataset - Arsalan Emami-Khoyi (Data in Brief, 2024)
The application of faecal DNA in genetic studies of wild populations minimises disturbances to their normal behaviours and body integrity. Here, I present an analysis of a metagenomic dataset generated from the faecal DNA of several specimens of the estuarine pipefish, Syngnathus watermeyeri, to simultaneously assemble the mitogenomes of the predator and its main prey species, the copepod Pseudodiaptomus hessei. The mitogenomes of the pipefish and the copepod were successfully reconstructed using a combination of short seed extension and denovo metagenomic assembly. Nucleotide blast searches of the circular contigs, mitogenome annotations, and Bayesian phylogenetic analyses confirm the completeness and correct taxonomic placements of the two mitogenomes. In addition, heteroplasmy detection and Pool-Seq variant calling quantified the level of genetic diversity in the sequences that formed these assemblies. These can be used as a first step to non-invasively survey genetic diversity in these populations.